The Assessment of Environmental Impact of the Chicken Meat Agroindustry in Indonesia: Life Cycle Assessment (LCA) Perspective - S. Azmi; Suprihatin; N. S. Indrasti; M. Romli (Faculty of Animal Science, Bogor Agricultural University, 2023)
Chicken meat agroindustry is one of the industries that contribute to environmental impacts. The environmental impacts are due to the use of resources, energy, and waste along the chicken meat chain. This study aimed to evaluate the environmental impacts along the life cycle of the chicken meat chain from cradle-to-grave using a life cycle assessment (LCA) approach. The data inventory consisted of inputs and outputs from five sub-systems: feed production, broiler production on the farm, carcass production at the slaughterhouse, supplier distribution, and consumer use. The impact categories included global warming, acidification, and eutrophication. The process of impact calculation used the CML-IA (Centre of Environmental Science of Leiden University Impact Assessment) baseline method on the SimaPro software. The results showed that consuming 1 kg of fried chicken resulted in a global warming impact of 5.86 kg CO2 eq, acidification of 38.3 g SO2 eq, and eutrophication of 24.1 g PO43- eq. Feed production, litter, and energy usage were the most significant contributors to the environmental impacts. Improvement scenarios in reducing environmental impacts included reducing crude protein in feed, composting litter, installing inverters on refrigeration compressors, and electrical energy efficiency. The present study indicated the importance of environmental impact assessment on the entire chicken meat chain to improve environmental performance in the Indonesian chicken agroindustry.